Agent-based modeling and simulation of a small scale cyber-physical system using NetLogo - Barbosa, José (2018)
The Cyber-Physical System (CPS) paradigm promotes the decentralization and distribution of the logic control as well as the integration of cyber and physical counterparts. In parallel, self-organization allows the dynamic and automatic system re-configuration responding to condition and environment changes. Modeling and simulation assume a crucial importance in the design of such complex, distributed, and self-organized systems, in the way that the detected and debugged errors may be corrected before the deployment into the real system, as well different strategies can be tested and evaluated. Agent-based modeling tools are computational frameworks able to analyze, experiment and compare systems populated by cooperative agents, supporting the fast prototyping of agent-based solutions exhibiting self-* properties. In this paper, the NetLogo tool was used to model and simulate the agent-based control layer of a small scale CPS, which control uses self-organization principles.